Influence of a passive exoskeleton on kinematics, joint moments, and self-reported ratings during a lifting task - Arauz, Paul G.; Chavez, Guillermo; Reinoso, Valentina; Ruiz, Pablo; Ortiz, Esteban; Cevallos, Carlos; Garcia, Gabriela (Journal of biomechanics, 2024)
It was found that the Auxivo LiftSuit reduced the load on the back and hip muscles when lifting heavy loads, but its effect on lower body kinematics, joint moments, and self-reported ratings was unclear. The purpose of this study was to assess the effect of this passive lift-exoskeleton design, on lower body kinematics, joint moments, and self-reported ratings during lifting of heavy loads. Twenty healthy subjects performed lifting of heavy loads with and without the exoskeleton under surveillance of a motion capture system. Medium and maximum level adjustments of the exoskeleton, as well as no exoskeleton use were analyzed. Our results indicate significant reduction (p <.01) in pelvis segment tilt and hip flexion ROM with the exoskeleton at maximum level adjustment in males during lifting. Lumbosacral flexion moment ranges were significantly decreased (p <.013) with the exoskeleton at maximum and medium level adjustment in males during lifting. The general user impressions were mostly positive, with participants reporting that it was easier to perform the task with the exoskeleton than without it (p <.0.001), and preferring and recommending the exoskeleton for the task. Although our findings may suggest negative effects of the Auxivo LiftSuit in males and females due to a ROM restriction and loose fit, respectively, it does not mean that the Auxivo LiftSuit is not useful for lifting tasks. Further design improvements are required to allow full range of motion of hips and pelvis, as well to provide better adjustment and level of support in female users.